Investigating the effects of ultrasonic waves and nanosilica on the viscosity reduction of Sharqy Baghdad heavy crude oil - Athraa W. Azeez; Hussein Q. Hussein (Iraqi Journal of Chemical and Petroleum Engineering)
The current study examines the combined impacts of ultrasonic waves and nano silica (NS) on reducing the viscosity Sharqy Baghdad heavy crude oil with an API gravity of 20.32. NS of an average particle size of 59.93 nm and 563.23 m²/g surface area were produced utilizing the sol-gel technique from Iraqi sand. The XRD analysis indicates the existence of an amorphous silica, the SEM analysis showed that NS tends to agglomerate, and the FTIR spectra exhibited the presence of siloxane and silanol groups. In addition, the TGA analysis demonstrated a total weight loss of 15.62%, validating the thermal stability of the NS. The experiments included a study of the impact of ultrasonic power, exposure time, duty cycle, temperature, and the combined effects of the ultrasonic waves and silica nanoparticles on the degree of viscosity reduction percentage (DVR%). The results demonstrated that the viscosity of the heavy crude oil decreased by 27.83% at an irradiation time of 2 min, power of 360 W, 0.8 duty cycle, a temperature of 35 ⁰C, assisted by nano silica at a concentration of 1500 mg/L.